Testing on weak-form of efficient market hypothesis of FTSE Bursa Malaysia Kuala Lumpur composite index (FBMKLCI) share index / Nur Syahidah Ishak - Ishak, Nur Syahidah (2017)
The market efficiency used to clarify the relationship between the information and stock prices. If the market price of any stocks reflected correctly and completely all relevant information, the market is still considered efficient. The financial market must be efficient so that it can take its role in terms of attracting investment, the Efficient Market Hypothesis (EMH) developed firstly by Paul Sammuelson in 1965 and Fama in 1970. The aims of this paper focus on to examine at the weak-form of the EMH. The weak form show that current stock market prices are fully reflects all stock market information including historical price. The problem is whether the price of FTSE Bursa Malaysia KLCI (FBMKLCI) Stock Index in Malaysia Stock Market is efficient in the weak form of Efficient Market Hypothesis? The main objective of this study is to justify weak-form of market efficiency of FTSE Bursa Malaysia KLCI (FBMKLCI) Stock Index in Malaysia Stock Market. Furthermore, the study is conducted to study whether the indexes follow the Random Walk hypothesis or not. The variable in this study is the stock market index of the FTSE Bursa Malaysia KLCI (FBMKLIC) Stock Index in Malaysia Stock Market. The samples in this study include daily, weekly and monthly closing price of the index. The analysis is observed in the range of 5 year in daily, weekly and monthly observation start from January 2012 to December 2016 with total number of 1300 observations for daily sample, 260 observations for weekly sample and 60 observations for monthly sample. The statistical test applied in this study is Descriptive Statistic, Augmented Dickey Fuller (ADF) Unit Root Test, Philips-Perron (PP) Unit Root Test, Autocorrelation Test and Runs Test.